Three-dimensional imaging of waves and floes in the marginal ice zone during a cyclone - Alberello A.; Bennetts L. G.; Onorato M.; Vichi M.; MacHutchon K.; Eayrs C.; Ntamba B. N.; Benetazzo A.; Bergamasco F.; Nelli F.; Pattani R.; Clarke H.; et al. (Nature Communications, 2022)
The marginal ice zone is the dynamic interface between the open ocean and consolidated inner pack ice. Surface gravity waves regulate marginal ice zone extent and properties, and, hence, atmosphere-ocean fluxes and ice advance/retreat. Over the past decade, seminal experimental campaigns have generated much needed measurements of wave evolution in the marginal ice zone, which, notwithstanding the prominent knowledge gaps that remain, are underpinning major advances in understanding the region’s role in the climate system. Here, we report three-dimensional imaging of waves from a moving vessel and simultaneous imaging of floe sizes, with the potential to enhance the marginal ice zone database substantially. The images give the direction–frequency wave spectrum, which we combine with concurrent measurements of wind speeds and reanalysis products to reveal the complex multi-component wind-plus-swell nature of a cyclone-driven wave field, and quantify evolution of large-amplitude waves in sea ice.